Development of Rotaxanes as E-Field-Sensitive Superstructures in Plasmonic Nano-Antennas - Jucker, Laurent; Ochs, Maximilian; Kullock, René; Aeschi, Yves; Hecht, Bert; Mayor, Marcel (Organic Materials, 2022)
We present the concept of electrostatic field-driven supramolecular translation within electrically connected plasmonic nano-antennas. The antenna serves as an anchoring point for the mechanically interlocked molecules, as an electrode for the electrostatic field, and as an amplifier of the antenna-enhanced fluorescence. The synthesis of a push–pull donor–π–acceptor chromophore with optical properties aligned to the antenna resonance is described and its immobilization on the surface is demonstrated. Photoluminescence experiments of the chromophore on a gold nano-antenna are shown, highlighting the molecule–antenna coupling and resulting emission intensity increase. The successful synthesis of an electrostatic field-sensitive [2]rotaxane in water is described and the tightrope walk between functionality and water solubility is illustrated by unsuccessful designs. In solution, an enhanced fluorescence quantum yield is observed for the chromophore comprising the mechanically interlocked [2]rotaxane in water and DMSO compared to the reference rod, ideal for future experiments in plasmonic nano-antennas.
Keywords: supramolecular chemistry; molecular switches; opto-electronic materials; nanoelectronics; nanotechnology